PERAN ISTRI NELAYAN DALAM MEMBANGUN KETAHANAN EKONOMI RUMAH TANGGA DI KABUPATEN BULUKUMBA - Roslindah Daeng Siang; Nurhaliza Nurhaliza; Akhmad Mansyur; Rosmawati Rosmawati; Sarini Yusuf (Jurnal Perikanan Pantura (JPP), 2024)
This study aims to find out the role of the fisherman's wife, the contribution of the fisherman's wife, and the level of household economic resilience. The research was carried out in the Sapolohe Village, Bonto Bahari District, Bulukumba Regency from May to June 2022. The determination of the research area was carried out purposively. Data were obtained through direct interviews with respondents using a questionnaire. The sample used in this study amounted to 20 respondents using simple random sampling technique. The method used in this research is descriptive qualitative and quantitative methods. The results of this study indicate that the role of fishermen's wives in building household economic resilience is the domestic role and the public role. The contribution of fishermen's wives to the household is 40-59% and is in the medium category, and the level of household economic resilience with a percentage of 65% is in the medium category.